Short- and medium-term sectoral employment forecasts 2021-2027 - Robert Stehrer (European Trade Union Institute (ETUI), 2022)
This working paper provides forecasts of changes in employment levels, in total, by sector and by different labour force groups in Europe, from 2022 to 2027. These forecasts of employment levels, both in terms of persons employed and in terms of hours worked, have been produced under three different scenarios, a baseline, an optimistic and an adverse one. These scenarios incorporate assumptions about possible developments such as the evolution of the war in the Ukraine and their impact on energy prices and inflation, the evolution of the Covid-19 pandemic and any public health measures they may trigger, and developments in the EU economic governance and the policy responses of the ECB to inflation, all of which are expected to influence output growth. These developments are linked with different projections about output growth from 2022 to 2027 and their likely translation into sectoral output demand trends. For example, a reform in EU economic governance which would result in requirements on member states to reduce their public debt too fast through budget surpluses, or too sharp a tightening of the monetary policy of the ECB would be associated with slower output growth or outright recession. Our baseline scenario is based on the output growth forecasts of the European Commission in July 2022 for 2022-2023 and on the IMF output growth forecasts for the years thereafter.
Keywords: 330; Arbeitsmarktprognose; Branche; Szenariotechnik; EU-Staaten; Europa